Mucormycosis causing pulmonary artery aneurysm - Lakshman Ramachandran; Sandeep Dewan; Vishal Kumar; Bhushan Wankhade (Respiratory Medicine Case Reports, 2015)
Pulmonary artery aneurysm (PAA) is an uncommon entity and is usually congenital in origin or secondary to pulmonary arterial hypertension. Infections causing PAA are few, tuberculosis and bacterial infections being the common causative organisms. There have been few cases reported previously, in which the organism causing PAA was found to be a rare fungus called mucor. Pulmonary mucormycosis causing PAA is an infrequent and almost fatal complication as most of the diagnosis was made post mortem. This report brings out a case of pulmonary mucormycosis causing ruptured PAA in a patient with diabetes. This patient was cured by a timely treatment of a combination of surgery and medical therapy.